2017
DOI: 10.1016/j.jhin.2016.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of infection associated with external ventricular drains: proposed methodology and results from a pilot study

Abstract: Routine and ongoing monitoring of patients with an EVD in situ to detect meningitis/ventriculitis presents logistical difficulties, and few units do so. This pilot study suggests that a national system of surveillance with agreed definitions and a methodology to enable unit-to-unit comparisons of EVD meningitis/ventriculitis is both necessary and feasible. This will, in turn, inform quality improvement processes leading to the minimization of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 22 publications
0
5
1
Order By: Relevance
“…During an IC intervention to improve staff adherence to IC practices, we observed that the infection rate decreased from 17.3 per 1000 drain days before the intervention to 7.9/1000 after the intervention. Our rate of EVD-related meningitis specifically, during and following the intervention period (9.5-8.6/1000 EVD days), was in the low range of rates in previous studies reporting on EVD-related meningitis per catheter day (4.8-17.2/1000 EVD days) in the UK and Ireland [12], Russia [27], and Switzerland [32]. In the analysis per patient, patientrelated factors dominated, while the effect of the IC intervention was observed in the analysis per catheter.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…During an IC intervention to improve staff adherence to IC practices, we observed that the infection rate decreased from 17.3 per 1000 drain days before the intervention to 7.9/1000 after the intervention. Our rate of EVD-related meningitis specifically, during and following the intervention period (9.5-8.6/1000 EVD days), was in the low range of rates in previous studies reporting on EVD-related meningitis per catheter day (4.8-17.2/1000 EVD days) in the UK and Ireland [12], Russia [27], and Switzerland [32]. In the analysis per patient, patientrelated factors dominated, while the effect of the IC intervention was observed in the analysis per catheter.…”
Section: Discussioncontrasting
confidence: 55%
“…The estimated ventriculostomy-related infection incidence rates range between 0 and 27% [9,12,22,26,28], the wide range being both real and artefactual due to differences in infection definitions. A few previous studies have addressed LD-related infection and rates ranging from 3 to 10% [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Ventriculitis most commonly occurs as a complication of external ventricular drains or in patients with ventricular shunts used to relieve increased intracranial pressure associated with hydrocephalus. Such infections are not uncommon (infection rate of ventricular-catheter raising up to 20% in some series) and are caused by microorganisms involved in foreign body infections such as staphylococci or antibiotic resistant Gram-negative bacilli [ 1 3 ] .…”
Section: Backgoundmentioning
confidence: 99%
“…External ventricular drain External ventricular drain (EVD)-associated bacterial ventriculitis is a frequent complication in patients with EVDs [1][2][3]. EVDs are used in neurocritical care units for monitoring of intracranial pressure, intrathecal drug administration, or drainage of cerebrospinal fluid (CSF).…”
Section: Introductionmentioning
confidence: 99%